1989
DOI: 10.1016/0014-5793(89)81367-5
|View full text |Cite
|
Sign up to set email alerts
|

The detection of natural opal suppressor seryl‐tRNA in Escherichia coli by the dot blot hybridization and its phosphorylation by a tRNA kinase

Abstract: It was believed that there was no natural suppressor tRNA in Escherichiu coli, however, it has been suggested that selC', relating to the synthesis of formate dehydrogenase of a selenoprotein [(1988) Nature 331, 723-7251, codes for tRNA, even though the presence of tRNA has not yet been demonstrated. We detected the product of se/C in the tRNA preparation of the E. cofi MC 4100 strain by the dot blot hybridization method with a DNA probe (ACCGCTGGCGGC) corresponding to the extra arm of sefC tRNA. Two hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The modification patterns of the hybrids at the low Na+ concentration (lanes [4][5][6][7][8] were mostly similar to those at the high Na+ concentration. A62, A64, A66 and A67 became more intensely modified in the hybrid with A4 (lane 4 and 6).…”
Section: Characterization Of the Hybridized Statementioning
confidence: 87%
See 1 more Smart Citation
“…The modification patterns of the hybrids at the low Na+ concentration (lanes [4][5][6][7][8] were mostly similar to those at the high Na+ concentration. A62, A64, A66 and A67 became more intensely modified in the hybrid with A4 (lane 4 and 6).…”
Section: Characterization Of the Hybridized Statementioning
confidence: 87%
“…In this regard, we have already reported specific and quantitative detection of a single tRNA species by a filter hybridization method, and the purification of some mitochondrial tRNAs by fusing this sensitive assay system and conventional open column chromatography [3,4]. This system was also used by others in order to quantitatively detect cellular suppressor serine tRNAs in dystrophic mouse muscle and in E. coli [7,8]. However, in the course of applying this procedure to other mitochondrial and nonmitochondrial tRNAs, some oligodeoxyribonucleotide probes were found not to hybridize to the corresponding tRNA species.…”
Section: Introductionmentioning
confidence: 99%
“…After activation at the hydroxyl group, the leaving group is replaced by a selenol moiety to yield selenocysteinyl-tRNAUe6A. In eukaryotes, it has been unequivocally demonstrated that the active serine derivative is 03-phosphoseryl-tRNA (28,29); the evidence presented by Mizutani et al (30) that E. coli selenocysteine formation also involves O-phosphorylation of L-serine is less compelling.…”
Section: Discussionmentioning
confidence: 98%
“…Experiments have yet to be presented which show that (i) the in vitro phosphorylation reaction is dependent on the presence of the selC-encoded tRNA and (ii) the phosphorylated product is identical with O-phosphoserine ester-bonded to tRNA (30).…”
Section: Discussionmentioning
confidence: 99%
“…The minor phosphoseryl-tRNA and another minor seryl-tRNA identified in bovine, rabbit, and chicken livers that decoded the stop codon UGA (12) were shown to be Sec tRNA [Ser]Sec (13). It was subsequently reported that phosphoseryl-tRNA [Ser]Sec was the intermediate in the biosynthesis of Sec in mammals (21,22) and in bacteria (23). However, after the identification of aminoacryltRNA [ (26).…”
Section: Discussionmentioning
confidence: 99%